Regarding "Shifting Sands" (Fall 2010) - Charles D. James (Issues in Science and Technology Librarianship)
A letter to the editor is presented in response to the article "Shifting Sands: Science Researchers on Google Scholar, Web of Science and PubMed With Implications for Library Collections Budgets," published in a previous issue of "Issues in Science and Technology Librarianship.